Technical, Pure Technical and Scale Efficiency: A Non-Parametric Approach of Pakistans Insurance and Takaful Industry - Taib, Che Azlan; Ashraf, Muhammad Saleem; Ahmad Razimi, Mohd Shahril (Allied Business Academies, 2018)
In this modern era of advanced technology, financial sector becomes a backbone of each and every economy. The financial sector is playing its significant role in mitigating the risk factors but the risk is the main ingredient of most of the business ventures. On the other hand stock market provides the investment opportunities to its investors. The financial chaos of 2007-2008 changed the worldview of the financial market (Harrington, 2009). Thus, experts are compelled to think about the alternative system rather than the conventional one. Islamic financial system, considered as alternative system got more attention than the other alternatives which are available in the financial market. Islamic financial institutions have shown their resilience during the financial distress of 2007-2008. Financial gurus, experts, academicians and policymakers are keen to analyse the different dimensions of the Islamic financial systems and they have shown their interest in the development of the different products and innovations (Chapra, 2011). Currently most of the Islamic Financial Institutions are launching new products which are compatible with the prevailing conventional system; most of their products are asset-based or Sharī’ah compliant. Almost 20% annual growth of Islamic finance has been observed (Chapra, 2008).